2014
DOI: 10.3103/s1068371214040117
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of communication lines with pulse-width and pulse-frequency-width data carriers. Theory and practice

Abstract: The noise immunity of lumped parameter communication lines transmitting pulse width and pulse frequency width signals with various modulation laws is analyzed. Basic analytical expressions and dynamic state spaces of communication lines operating in the presence of induced harmonic interference with a wide frequency range are given. It is shown that the lines with pulse frequency width data carriers exhibit the highest noise immunity. Block diagrams and waveform diagrams of pulse frequency width scan ning conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In the core of the integrating PLL lies a continuous structure of an integrating scanning converter with pulse-frequency-width modulation (PFWM) [13,16], which consists of adders 1-2, an integrator I and a relay element (RE) with a hysteresis loop (fig. 1a) of 'zero' relative symmetry and which works in outer synchronization with the supply-line voltage mode [13].…”
Section: Static and Dynamic Characteristics Of The Integrating Pllmentioning
confidence: 99%
See 1 more Smart Citation
“…In the core of the integrating PLL lies a continuous structure of an integrating scanning converter with pulse-frequency-width modulation (PFWM) [13,16], which consists of adders 1-2, an integrator I and a relay element (RE) with a hysteresis loop (fig. 1a) of 'zero' relative symmetry and which works in outer synchronization with the supply-line voltage mode [13].…”
Section: Static and Dynamic Characteristics Of The Integrating Pllmentioning
confidence: 99%
“…Numerous studies conducted by the authors showed that applying the methods of integrating scanning conversion for designing both synchronizing units and semiconductor inverter control systems on the whole is one of the most effective ways of improving their noise immunity, the static and dynamic accuracy [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%